2012
DOI: 10.1186/1748-5908-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences on the feasibility, acceptability, and use of malaria rapid diagnostic tests at peripheral health centres in Uganda-insights into some barriers and facilitators

Abstract: BackgroundWhile feasibility of new health technologies in well-resourced healthcare settings is extensively documented, it is largely unknown in low-resourced settings. Uganda's decision to deploy and scale up malaria rapid diagnostic tests (mRDTs) in public health facilities and at the community level provides a useful entry point for documenting field experience, acceptance, and predictive variables for technology acceptance and use. These findings are important in informing implementation of new health tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
113
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(117 citation statements)
references
References 20 publications
4
113
0
Order By: Relevance
“…The highly positive perceptions of RDTs demonstrated by patients in this study correspond closely with other similar studies conducted in Ghana, Tanzania and Uganda [20,21,23-25]. Others have also identified that RDT acceptability is based on its perceived role in aiding the clinician to reach a more definitive diagnosis and prescribe the right treatment for their illness [20,23].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The highly positive perceptions of RDTs demonstrated by patients in this study correspond closely with other similar studies conducted in Ghana, Tanzania and Uganda [20,21,23-25]. Others have also identified that RDT acceptability is based on its perceived role in aiding the clinician to reach a more definitive diagnosis and prescribe the right treatment for their illness [20,23].…”
Section: Discussionsupporting
confidence: 85%
“…Others have also identified that RDT acceptability is based on its perceived role in aiding the clinician to reach a more definitive diagnosis and prescribe the right treatment for their illness [20,23]. The value of the test in communicating a patient’s ‘problem’ to the clinician more clearly than they could verbally, has also been reported elsewhere [24].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, RDTs also raised conflicts over their own clinical judgement for clinicians in Ghana [12], as was reported previously with microscopy in Tanzania [10]. The narratives employed by health workers in this study to cope with this conflict, which undermined the usefulness, accuracy and relevance of these tests, have also been reported elsewhere, for example in Uganda [58]. Dealing with this conflict posed by RDTs through identifying alternative disease(s) has also been reported in different settings, while simultaneously drawing attention to the lack of support for diagnosing and treating alternative causes across settings with different levels of malaria transmission [12,58-60].…”
Section: Discussionsupporting
confidence: 62%